Deploying DNSSEC in islands of security - Murisa, Wesley Vengayi (Rhodes University, Faculty of Science, Department of Computer Science, 2013)
The Domain Name System (DNS), a name resolution protocol is one of the vulnerable network protocols that has been subjected to many security attacks such as cache poisoning, denial of service and the 'Kaminsky' spoofing attack. When DNS was designed, security was not incorporated into its design. The DNS Security Extensions (DNSSEC) provides security to the name resolution process by using public key cryptosystems. Although DNSSEC has backward compatibility with unsecured zones, it only offers security to clients when communicating with security aware zones. Widespread deployment of DNSSEC is therefore necessary to secure the name resolution process and provide security to the Internet. Only a few Top Level Domains (TLD's) have deployed DNSSEC, this inherently makes it difficult for their sub-domains to implement the security extensions to the DNS. This study analyses mechanisms that can be used by domains in islands of security to deploy DNSSEC so that the name resolution process can be secured in two specific cases where either the TLD is not signed or the domain registrar is not able to support signed domains. The DNS client side mechanisms evaluated in this study include web browser plug-ins, local validating resolvers and domain look-aside validation. The results of the study show that web browser plug-ins cannot work on their own without local validating resolvers. The web browser validators, however, proved to be useful in indicating to the user whether a domain has been validated or not. Local resolvers present a more secure option for Internet users who cannot trust the communication channel between their stub resolvers and remote name servers. However, they do not provide a way of showing the user whether a domain name has been correctly validated or not. Based on the results of the tests conducted, it is recommended that local validators be used with browser validators for visibility and improved security. On the DNS server side, Domain Look-aside Validation (DLV) presents a viable alternative for organizations in islands of security like most countries in Africa where only two country code Top Level Domains (ccTLD) have deployed DNSSEC. This research recommends use of DLV by corporates to provide DNS security to both internal and external users accessing their web based services.,LaTeX with hyperref package,pdfTeX-1.40.10
Keywords: Internet domain names; Computer security; Computer network protocols; Computer security -- Africa